Morphological Process Of Neologism Found In Social Networking Jargon: Array - Pratama, Muhammad Ekky Singgih; Idris, Zuindra; Simamora, Taufik Hidayat; Tampubolon, Jamsen Salomo (Universitas Harapan Medan, 2021)
This study is aimed to reveal and define the new words that have been created in this new modern era by using social networking. The Neologism itself has their own stability, even though the words are not put in dictionary. Moreover, this study explained how the morphological process in words could create newly coinage words nowadays. The writer proposed Newmark theory as the grand theory to researched the newly coinage words and as the main foundation in making this study. For this study, the writer used social networking as the main object. The data were obtained from any social chatting relay such as Facebook, Twitter, Messenger, Instagram and IRC. Some data were taken from the journals that has specific contents about Neologism as well. The writer has described the words related to Neologism in changing by formation. The results are; the writer found 130 newly coinage total words for nine types of Neologism which are Blending (31 words, 23,84%), Abbreviations (7 words, 5,38%), Coinage (6 words, 4,61%), Acronym (41 words, 31,53%), Clipping (11 words, 8,46%), Affixation (26 words, 20%), Eponym (2 words, 1,53%), Conversion (5 words, 3,84%), Collocation (1 word, 0,76%). As the final result and objective, the writer has concluded that Acronym is the most dominant type of Neologism that found in social networking.